Impact Of Village Financial Implementation On Village Financial Management Accountability - Agung Nur Probohudono, Indrian Supheni, Rahmawati, (Jurnal Ekonomi, 2019)
Accountability in the implementation and management of village finance is very important. Requires the village government to manage village finance professionally, effectively and efficiently, and responsibly. One source of village income that functions as a source of village operational activities and for community empowerment is the Village Fund. With the receipt of this fund, the village government must be prepared and able to manage village finance based on the principles of transparency, accountability, and participation in accordance with Minister of Home Affairs Regulation No. 113 of 2014. The purpose of this study is to determine the effect of village finance on village financial management accountability. The subject of this study was the village government in East Java. The sample in this study were 374 villages. The results show that the implementation of income receipts, expenditure implementation, and financing implementation have a significant influence on the accountability of village financial management.Â